PRCD is essential for high-fidelity photoreceptor disc formation - Spencer, William J. (Proc Natl Acad Sci U S A, 2019)
Progressive rod-cone degeneration (PRCD) is a small protein residing in the light-sensitive disc membranes of the photoreceptor outer segment. Until now, the function of PRCD has remained enigmatic despite multiple demonstrations that its mutations cause blindness in humans and dogs. Here, we generated a PRCD knockout mouse and observed a striking defect in disc morphogenesis, whereby newly forming discs do not properly flatten. This leads to the budding of disc-derived vesicles, specifically at the site of disc morphogenesis, which accumulate in the interphotoreceptor matrix. The defect in nascent disc flattening only minimally alters the photoreceptor outer segment architecture beyond the site of new disc formation and does not affect the abundance of outer segment proteins and the photoreceptor’s ability to generate responses to light. Interestingly, the retinal pigment epithelium, responsible for normal phagocytosis of shed outer segment material, lacks the capacity to clear the disc-derived vesicles. This deficiency is partially compensated by a unique pattern of microglial migration to the site of disc formation where they actively phagocytize vesicles. However, the microglial response is insufficient to prevent vesicular accumulation and photoreceptors of PRCD knockout mice undergo slow, progressive degeneration. Taken together, these data show that the function of PRCD is to keep evaginating membranes of new discs tightly apposed to each other, which is essential for the high fidelity of photoreceptor disc morphogenesis and photoreceptor survival.